Big Data Dan Statistik: Transformasi Administrasi Publik Di Era Digital - Mozin, Sri Yulianty; Napu, Febriany Hasnawati; Anggraini, Maya; Amanda, Ni Made; Rifkin; Rumampuk, Fardan; Abas, Adam (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
The digital world has changed the way public administration is conducted. Big data and statistics greatly assist data-driven decision-making. Continuous data from various sources, such as public surveys, government transactions, social media, and sensors, enable the government to improve efficiency and enhance public services. The collection, storage, and analysis of large-scale data can be done quickly thanks to Big Data. Hidden patterns can be identified to support the formulation of more targeted policies using statistical methods. Descriptive analysis helps understand the socio-economic conditions in various regions, while predictive analysis helps forecast future public service needs. In addition, open data visualization through interactive dashboards allows the public to see government performance in real-time, increasing accountability and boosting public trust. But issues such as data privacy, information security, and a lack of human resources remain problematic. This article discusses how statistics and Big Data enhance the efficiency, transparency, and accountability of public administration. It also provides policy recommendations on the best ways to leverage this technology.